Parenting in the 21st Century - Buchanan, Christy; Glatz, Terese (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this Special Issue, we present a collection of articles that cover the unique opportunities and challenges of parenting in the 21st century. We have identified three themes across the articles: managing stress; support for effective parenting; and emphasis on fostering competence for an uncertain future. First, although the studies did not use data to test for differences between cohorts of parents, the results suggested that stress is a normal state for parents today, and especially for certain groups of parents. Second, despite high stress among parents, the articles point at some important support systems for parents in the 21st century. For example, although technology can be a stressor, it can also be a useful tool to enhance the parent-child relationship for parents of adolescents or young adults. Finally, in the third theme, we saw an emphasis on promoting a mix of competencies emphasizing both autonomy and relatedness in children and speculate that parents see these competences as tools to help the child to deal with an uncertain future.Results from this Special Issue illustrate the impact of societal changes on parenting. The findings can be used to develop programs and policies to provide support to diverse parents in handling today's stressors, ranging from technology to racism to excessive pressures for parental "success". They also point to important research gaps in understanding the task of parenting in the 21st century.